2021
DOI: 10.1016/j.cell.2021.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Emergency drug use in a pandemic: Harsh lessons from COVID-19

Abstract: The scientific and clinical communities have both experienced several harsh lessons on clinical care management and drug development during the COVID-19 pandemic. Here, we discuss several key lessons learned and describe a framework within which our two communities can work together and invest in to improve future pandemic responses. ll

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In patients with severe COVID-19 pneumonia, broad dysregulated immune responses have been identified with patients showing elevations in a range of proinflammatory cytokines [ 11 18 ]. These pathophysiologic events suggest that treatments with broad-based immunomodulatory effects may be more effective in treating COVID-19 pneumonia than those targeting specific immune pathways to prevent disease progression [ 11 19 ]. One such potential treatment is Auxora, a calcium release-activated calcium (CRAC) channel inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with severe COVID-19 pneumonia, broad dysregulated immune responses have been identified with patients showing elevations in a range of proinflammatory cytokines [ 11 18 ]. These pathophysiologic events suggest that treatments with broad-based immunomodulatory effects may be more effective in treating COVID-19 pneumonia than those targeting specific immune pathways to prevent disease progression [ 11 19 ]. One such potential treatment is Auxora, a calcium release-activated calcium (CRAC) channel inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies showed that some patients infected with SARS-CoV-2 developed severe pneumonia and ARDS (Grant et al, 2021 ). Consequently, both antiviral and immunomodulatory drugs were contemplated and administered early in the pandemic (Martinez, 2020 ; Cross et al, 2021 ). Early studies (Tay et al, 2020 ) searched for parallelisms between SARS-CoV-2-related pneumonia and pneumonias connected to other human coronavirus diseases, such as severe acute respiratory syndrome (SARS-CoV) and Middle East respiratory syndrome (MERS-CoV).…”
mentioning
confidence: 99%
“…However, the pathobiology of SARS-CoV-2-related pneumonia seems to be distinct from pneumonia caused by other respiratory viral and bacterial pathogens; the SARS-CoV-2-related pneumonia displays unusual clinical features and has a longer clinical course than severe pneumonia (Gattinoni et al, 2020 ; Grant et al, 2021 ). An accurate clinical characterization of SARS-CoV-2 infections, based on known clinical syndromes, is critical for the identification of effective therapies (Cross et al, 2021 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations